Effect of elevated CO2 concentration on groundnut (Arachis hypogaea) (C3) and pearl millet (Pennisetum glaucum) (C4) crop plants and some implications on growth and photosynthetic activity - VARDHAN, D ASHOK; VANAJA, M; SRINIVAS, K; LAL, MUNNA; SATISH, T; REDDY, PURUSHOTHAM (The Indian Journal of Agricultural Sciences, 2026)
Groundnut (Arachis hypogaea L.) (C3) and pearl millet (Pennisetum glaucum L.R. Br. emend Stuntz) (C4) crop plant species were grown in open top chambers (OTC) to find out performance at ambient CO2 (380 ppm) and elevated CO2(550Â±700 ppm) atmospheric CO2 conditions.Compared with an elevated CO2 atmosphere at ambient leaf water content increased in C4 plants. But was the same or less for the C3 plants. Groundnut (C3) leaf mass per unit area was less for C4 plants and greater for a C3 species. At elevated study photosynthesis gas exchange (pn) values were the same for C4 plants and were greater for C3 plants. While stomatal conductances were reduced in all comparison compared to plants at ambient and elevated CO2 levels. Short term photosynthetic value taken immediately after swiching treatments were not significantly different from long term values for the same treatments. In all tested species gas conduct values were lowered when measured directly after being transferred to the other treatments. Continual gas exchange measurements for up to 90 minutes after a transfer from long term elevated CO2 enrichment to ambient and back indicated that the short term Pn value for C4 species. The chlorophyll a and b accumulation were also higher in the leaves of both C3 and C4 crop plants to increased elevated CO2.As pointed out above in the switching experiments had not equilibrated to change in the treatment. Whereas C4 plants had photosynthetic activity at elevated CO2 continued at a rapid pace throughout the day for the C3 plants. That for the same as at ambient levels. The decrease in Pn at elevated CO2 suggested non-stomatal control in the C3 plants.